(untitled) (International Journal of Engineering and Computer Science, 2015)
Although tremendous progress has made in the past years to eliminate the inter-block interference (IBI) but still it is considered as area of concern in orthogonal frequency division multiplexing system. We proposed interference alignment based channel independent precoding in MIMO OFDM system. We showed that when the number of receive antennas (nr) is not more than the number of transmit antennas (nt), our proposed precoding is more bandwidth efficient than the conventional zero-padded or CP added MIMO systems, such as, ZP-only, CP-OFDM and SC-FDE system and When the number of receive antennas is more than the number of transmit antennas, it was shown that the IBI in an MIMO OFDM system can be completely eliminated without any CP or zero-padding or precoding, when the OFDM block size is not too small. In this paper, we consider only CP based block transmission system.